Comparative Study of the Combined Antibacterial Effects of Grape Seed and Cranberry Fruit Extracts on Extended-Spectrum Beta-Lactamase (ESBL)-Producing Escherichia coli: Antibacterial Effects of Grape Seed and Cranberry Extracts - Bijarani, Ali Nawaz; Sultana, Ulfat; Iqbal, Nasima; Naeem, Nabeela; Irshad, Sidra; Khadija Abbasi, Momina (Pakistan Journal of Health Sciences, 2024)
Antimicrobial resistance is a threat to global healthcare system. Therefore, there has been growing interest towards the natural plants which possess antimicrobial properties. Objective: The key goal of the current research is to find out the combined effect of cranberry fruit and grape seed extracts against Extended-Spectrum Beta-Lactamase (ESBL) Escherichia coli strains. Methods: E.coli bacteria with ESBL resistance were collected from the patient’s samples having bacterial infection. The extracts, grape seeds and cranberry fruits extract were prepared in different concentrations. Antibiotic susceptibility testing was done with different concentrations of the extracts, using agar dilution methods to assess their antibacterial efficacy against Meropenem and Linezolid. SPSS version 21.0 was used for data analysis. Results: The combined effect of cranberry fruit and grape seed extracts demonstrated significant antibacterial influence in counter to decrease ESBL E.coli strains. There were 40 specimens, with 45% female and 55% male, with an age range between 10 to 80 years old. Both the plant extract revealed high sensitivity against ESBL E.coli, with 95% sensitivity at the highest concentrations. The combination of CFE and GSE (50mg+60mg) showed more than 90% sensitivity, more than commonly used antibiotics like Meropenem and Linezolid. Conclusions: The combined effect of cranberry fruit and grape seed extracts showed excellent effect against antimicrobial resistance, particularly in ESBL-producing E.coli strains. The finding suggested the increase potential of natural products as alternative antimicrobial agents.